THE ROLE OF PSYCHOSOCIAL INTERVENTIONS IN THE REHABILITATION OF PATIENTS WITH SURGICAL INTERVENTIONS FOR ORAL CANCER - Iulia Olaru; Florin-Ştefan Olaru; Alexandra Boloș; Adriana Olaru (Romanian Society of Oral Rehabilitation, 2023)
The surgical interventions performed to treat oral cancer can cause important psychological manifestations, but also eating disorders, deglutition disorders, intense pain, sometimes severe depression or anxiety. That is why it is very important to understand as completely as possible the psychological and social deficiencies that patients diagnosed with oral cancer may encounter, in order to help them throughout the treatment, and throughout their survival. The implementation of measures to ensure the psychosocial adaptation to everything that involves a surgical intervention for the treatment of oral cancer needs to be done as early as possible. The goals of these interventions can be represented by the reduction of isolation, the feeling of alienation, anxiety, lack of hope and optimism regarding the future and the clarification or reinterpretation of erroneous information and thoughts about the disease and treatment. Accordingly, this work aims to highlight those measures that can be used to reduce the psychosocial consequences determined by the complex treatment and especially by the surgical intervention specific to oral cancer.